2013
DOI: 10.7205/milmed-d-12-00261
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Avoidant Personality Traits in a German Armed Forces Inpatient Psychiatric Setting

Abstract: Military duty places high demands on the soldiers' social adaptability and competences. Avoidant personality traits can lead to interpersonal conflicts and at least to mental disorders. 192 German Armed Forces soldiers were treated in a multimodal inpatient psychiatric treatment setting at a Bundeswehr hospital between 2007 and 2010. 129 of these patients received a social skills group training (group training of social competence [GSC]) as part of this setting. A comparison group (n=63) did not participate bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…The improvements in CBT were maintained at 6 months of follow-up. Social skills group training as a treatment component for patients with AvPD did not seem to have any additional effect on group treatment or individual treatment (Stravynski, Lesage, Marcouiller, & Elie, 1998;Zimmermann et al, 2013) In a naturalistic study of time-limited psychodynamic treatment with 52 sessions of Supportive-Expressive psychotherapy, Barber and co-workers found that 60% of the 24 patients with AvPD lost their PD diagnoses, compared with 85% of the 14 patients with…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…The improvements in CBT were maintained at 6 months of follow-up. Social skills group training as a treatment component for patients with AvPD did not seem to have any additional effect on group treatment or individual treatment (Stravynski, Lesage, Marcouiller, & Elie, 1998;Zimmermann et al, 2013) In a naturalistic study of time-limited psychodynamic treatment with 52 sessions of Supportive-Expressive psychotherapy, Barber and co-workers found that 60% of the 24 patients with AvPD lost their PD diagnoses, compared with 85% of the 14 patients with…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Examining personal values and moral beliefs and their impact on mental health following deployment has yielded clear indication of the importance of these topics in the context of traumatized soldiers ( 10 , 11 , 14 ). However, as this study’s approach combines elements of ACT, CBT, spiritual care, and AD therapy, the extent to which any of these approaches alone contributes to therapeutic effects remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to forgive oneself and others seems to be central to the concept of MI (8), leading to a shift in an individual's understanding of values and norms along with disturbances in selfreferential processing (9)(10)(11). Kopacz discusses MI as a "primary psychological injury" (12) that is not fully captured by the conventional diagnostic criteria of post-traumatic stress disorder (PTSD) but can instead be understood as a dimensional construct.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Roger presented with avoidant and depressive PD symptoms. Avoidant PD has been shown to be highly responsive to behavioral interventions, possibly due to a strong overlap with social anxiety disorder (Alden, 1989; Feske, Perry, Chambless, Renneberg, & Goldstein, 1996; Zimmermann et al, 2013). Patients with other forms of PD may be less responsive to behavioral strategies.…”
Section: Discussionmentioning
confidence: 99%